2006
DOI: 10.1111/j.1360-0443.2006.01648.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of assertive continuing care on continuing care linkage, adherence and abstinence following residential treatment for adolescents with substance use disorders

Abstract: are the two names I most associate with groundbreaking studies aimed at enhancing long-term recovery outcomes for adolescents following addiction treatment. They have done this through development of an approach to adolescent treatment (the Adolescent Community Reinforcement Approach) that seeks among other things to create a post-treatment family and social environment conducive to recovery and by pioneering assertive approaches to post-treatment continuing care for adolescents and their families. My own work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
200
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(206 citation statements)
references
References 43 publications
6
200
0
Order By: Relevance
“…There is a growing body of scientific evidence that suggests that posttreatment monitoring (recovery check-ups) and support can elevate recovery outcomes for adults [82,88,89] and adolescents [90][91][92]. Assertive approaches to continuing care are a hallmark of the RM model.…”
Section: Posttreatment Monitoring Support and Early Reinterventionmentioning
confidence: 99%
“…There is a growing body of scientific evidence that suggests that posttreatment monitoring (recovery check-ups) and support can elevate recovery outcomes for adults [82,88,89] and adolescents [90][91][92]. Assertive approaches to continuing care are a hallmark of the RM model.…”
Section: Posttreatment Monitoring Support and Early Reinterventionmentioning
confidence: 99%
“…Sixteen primary studies were included with young people aged 12-19 years. 81,105,[107][108][109][110][111][112][113][114][115][116][117][118][119][120] The studies included various interventions including BI, cognitive-behavioural therapy (CBT) and multidimensional family therapy 81,85,121,122 No information was given on the nature of the interventions; however, the number of sessions ranged from one to four. The age range included in the studies was 12-23 years.…”
Section: Primary and Secondary Prevention Interventions For Risky Drimentioning
confidence: 99%
“…The Cannabis Youth Treatment study (Dennis et al, 2004) tested treatment conditions across multiple settings (a combination of motivational enhancement and cognitive behavioral treatment compared with a family support network model), found similar results across the three conditions, and concluded that outcomes may have been driven more by general helping factors beyond the specific treatment approaches tested. Godley et al (2006) examined the critical role that aftercare plays in transitioning adolescents from brief intensive therapeutic settings to home environments in evaluating the effects of the assertive continuing care (ACC) program, and noted that ACC predicted superior early abstinence for adolescents with diagnosed substance use disorders. Despite these results suggesting successful research therapy implementation, challenges to providers still exist, leading to many promising interventions not being used by practitioners.…”
Section: Research On Adolescent Substance-abuse Treatment Outcomementioning
confidence: 99%